Core competencies of clinical nurse specialists: A comparison across three Nordic countries. Issue 23 (6th June 2021) - Jokiniemi, Krista; Hølge‐Hazelton, Bibi; Kristofersson, Gisli Kort; Frederiksen, Kirsten; Kilpatrick, Kelley; Mikkonen, Santtu
Abstract: Aim: To describe and compare the clinical nurse specialist core competency use in Finland, Denmark and Iceland. Background: Clinical nurse specialist roles were first developed more than 60 years ago in the United States. Within the Nordic countries, the clinical nurse specialist role emerged around 2000. There is scarcity of clinical nurse specialist competency descriptions outside of North America, and research has been limited to examine or validate established competencies across different countries. Design: A descriptive correlational study. Methods: An online survey was conducted from May to September 2019. A population sample of clinical nurse specialists in Finland, Denmark and Iceland was recruited. A validated self‐report questionnaire of clinical nurse specialist competencies was used. The data were analysed using descriptive and inferential statistics, and the STROBE checklist was used as the reporting guideline. Results: A total sample of 184 clinical nurse specialists, 52 from Finland, 95 from Denmark and 37 from Iceland, participated in the study (response rate = 72%, 35% and 48%, respectively). Overall, clinical nurse specialists utilised the organisational competency most frequently followed by the patient, clinical nursing leadership and scholarship competency. Univariate analysis of variance test between‐country effects showed statistically significant difference in patient competency ( p = .000) and in organisational competency ( p < .05). There were no statistically significant differences between counties in the utilisation of clinical nursing leadership and scholarship competency. Conclusion: A small variability was found in the comparison of the clinical nurse specialist use of core competency in the spheres of patient, nursing, organisation and scholarship within three Nordic countries. Relevance to clinical practice: The CNS competency scale may be utilised in benchmarking clinical nurse specialist roles and practice within and across countries. The long‐term goal for the competency descriptions is to enhance the clinical nurse specialist role clarity, integration and evaluation as well as inform post‐graduate education.